2017
DOI: 10.1007/s11307-017-1070-1
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and In Vitro and In Vivo Evaluation of [3H]LRRK2-IN-1 as a Novel Radioligand for LRRK2

Abstract: Purpose LRRK2 (leucine-rich repeat kinase 2) has recently been proven to be a promising drug target for Parkinson’s disease (PD) due to an apparent enhanced activity caused by mutations associated with familial PD. To date, there have been no reports in which a LRRK2 inhibitor has been radiolabeled and used for in in vitro or in vivo studies of LRRK2. In the present study, we radiolabeled the LRRK2 ligand, LRRK-IN-1, for the purposes of performing in vitro (IC50, Kd, Bmax, autoradiography) and in vivo (biodist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It may be important to determine if LRRK2 mutation carriers have an earlier increase in LRRK2 protein levels, similar to the early increase reported for idiopathic Parkinson’s disease brain ( Dzamko et al , 2017 ). Novel radioligands for LRRK2 may make such studies possible in the future ( Malik et al , 2017 ). Moreover, it will be important to determine the relationship between LRRK2 protein and LRRK2 kinase activity, studies that could potentially be achieved by measuring phosphorylation levels of recently described LRRK2 substrates, such as the Rab GTPases ( Steger et al , 2016 ), when suitable techniques become available.…”
Section: Discussionmentioning
confidence: 99%
“…It may be important to determine if LRRK2 mutation carriers have an earlier increase in LRRK2 protein levels, similar to the early increase reported for idiopathic Parkinson’s disease brain ( Dzamko et al , 2017 ). Novel radioligands for LRRK2 may make such studies possible in the future ( Malik et al , 2017 ). Moreover, it will be important to determine the relationship between LRRK2 protein and LRRK2 kinase activity, studies that could potentially be achieved by measuring phosphorylation levels of recently described LRRK2 substrates, such as the Rab GTPases ( Steger et al , 2016 ), when suitable techniques become available.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wang M. et al (2017) described the radiolabeling of [ 11 C]-HG-10-102-01 but as with the Roche/Genentech probes, no in vitro or in vivo PET characterization of this molecule was described. Malik et al (2017) reported that they had successfully radiolabeled [ 3 H]-LRRK2-IN-1, however, its use as a CNS PET tracer is limited by poor off-target selectivity and limited brain penetration of the base molecule. Most recently, Chen et al, 2019 reported on the development of [ 11 C]-GNE-1023 and reported excellent in vitro specific binding of [ 11 C]-GNE-1023 to LRRK2 in rat and NHP brain sections ( Chen et al, 2019 ).…”
Section: Current Assays Being Employedmentioning
confidence: 99%